2017
DOI: 10.1503/cmaj.161020
|View full text |Cite
|
Sign up to set email alerts
|

Use of antibiotics during pregnancy and risk of spontaneous abortion

Abstract: BACKGROUND: Although antibiotics are widely used during pregnancy, evidence regarding their fetal safety remains limited. Our aim was to quantify the association between antibiotic exposure during pregnancy and risk of spontaneous abortion. METHODS:We conducted a nested case-control study within the Quebec Pregnancy Cohort (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009). We excluded planned abortions and pregnancies exposed to fetotoxic drugs. Spontaneous abortion was defined as having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 32 publications
3
93
1
9
Order By: Relevance
“…During pregnancy, pharmacokinetic alterations in antibiotics require dose adjustment or careful monitoring and assessment [4, 23]. Antibiotic use during pregnancy has also shown a risk of spontaneous abortion and congenital malformations in the first trimester [2427]. …”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, pharmacokinetic alterations in antibiotics require dose adjustment or careful monitoring and assessment [4, 23]. Antibiotic use during pregnancy has also shown a risk of spontaneous abortion and congenital malformations in the first trimester [2427]. …”
Section: Discussionmentioning
confidence: 99%
“…Вот почему так важно диаду мать-дитя наблюдать бригадой спе-циалистов, включающей в обязательном порядке помимо акушера-гинеколога еще и педиатра, кото-рый не допустит назначения опасных для здоровья будущего человека антибиотиков без особых на то показаний! Кстати, есть данные и связи приема анти-биотиков с повышенным риском самопроизвольного выкидыша [22]. В своем исследовании канадские уче-ные из Монреальского университета, изучавшие данные о 182 369 беременных женщинах в возрасте 15-45 лет за период с 1998 по 2009 г., проживающих в провинции Квебек, установили, что применение антибиотиков уве-личивало риск самопроизвольных абортов: макролидов (азитромицина и кларитромицина) -на 67%, хинолонов, тетрациклинов, сульфаниламидов -на 65%, метронида-зола -на 70%.…”
Section: антибиотикорезистентность в современном миреunclassified
“…Several animal model studies have shown possible teratogenic effects. [14][15][16] In the present study we wished to further explore this topic by performing an updated literature search and metaanalysis of the human studies, and in this way provide practical guidance about the use of these agents in pregnancy. In 2009, Bar-Oz et al performed a meta-analysis of the available data regarding the effect of fluoroquinolones, taken during the first trimester, on fetal malformations and pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%